2015
DOI: 10.1002/pts.2141
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and Tough Poly(lactic acid) Films for Packaging Applications: Property and Processability Improvement by Effective Reactive Blending

Abstract: This study demonstrates a practical means to overcome inherent brittleness problem of poly(lactic acid) (PLA) and make PLA feasible as packaging material. PLA with suitable processability is utterly required for package manufacturers, where flexible, tough PLA film is essential for packers and end users. Highly flexible PLA films with 60-fold increase in elongation at break (Eb) over that of the neat PLA were successfully produced by integrating effective reactive blending and economical film blowing process. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 35 publications
0
28
0
2
Order By: Relevance
“…The cold crystallization temperature of the PLA in the films was decreased by 6°C, indicated that the PBAT enabled improvement of the crystallization ability of PLA in the films, as previously reported . From Figure , the peak of cold crystallization became wider with increasing PBAT content.…”
Section: Resultsmentioning
confidence: 99%
“…The cold crystallization temperature of the PLA in the films was decreased by 6°C, indicated that the PBAT enabled improvement of the crystallization ability of PLA in the films, as previously reported . From Figure , the peak of cold crystallization became wider with increasing PBAT content.…”
Section: Resultsmentioning
confidence: 99%
“…Poly(butylene adipate‐ co ‐butylene terephthalate (PBAT) is a copolymer of polybutylene adipate glycol (PBA) and polybutylene terephthalate (PBT). So, it not only has good impact resistance and heat resistance but also has good ductility and elongation at break . Hydroxyapatite (HA) is the main component of the bones and teeth of invertebrates and vertebrates.…”
Section: Introductionmentioning
confidence: 99%
“…So, it not only has good impact resistance and heat resistance but also has good ductility and elongation at break. 9,10 Hydroxyapatite (HA) is the main component of the bones and teeth of invertebrates and vertebrates. It has broad application prospects in many fields due to its good biocompatibility, adsorption, ion exchange, low crystallization temperature and good thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…The latter which can take full advantages of desirable component properties, such as high strength, thermoformability, and barrier properties, gradually becomes one of the most widely applied methods for heat‐shrink film fabrication. However, the improvement of TD performance of blown film depends on high blow‐up ratio (BUR) defined as the ratio of final film‐tube diameter to die diameter, apart from changing the die geometry . The draw‐down ratio (DDR) is defined as the ratio of film velocity at the nip roll to average velocity in the die.…”
Section: Introductionmentioning
confidence: 99%
“…However, the improvement of TD performance of blown film depends on high blow-up ratio (BUR) defined as the ratio of final film-tube diameter to die diameter, apart from changing the die geometry. 13,14 The draw-down ratio (DDR) is defined as the ratio of film velocity at the nip roll to average velocity in the die. Generally, DDR is larger than BUR in film blowing, making the performance of blown film along TD less than that along machine direction (MD).…”
mentioning
confidence: 99%